Radioligands for the dopamine receptor subtypes1. (24th April 2013) - Prante, Olaf; Maschauer, Simone; Banerjee, Ashutosh
<x xml:space="preserve">Abstract</x> The actions of the predominant neurotransmitter in the brain, dopamine, are mediated by the postsynaptic dopamine receptors. The five dopamine receptor subtypes and their regulation have been associated with a large variety of psychiatric diseases. Therefore, positron emission tomography (PET) imaging studies using suitable and selective 18F‐labeled and 11C‐labeled dopamine receptor radioligands could provide valuable knowledge on the impact of receptor density on the pathogenesis and evolvement of neuropsychiatric and neurological diseases. This special issue subchapter provides a summary of the most important 18F‐labeled and 11C‐labeled radioligands for PET imaging of the dopamine receptor subtypes, their radiochemistry, and characteristics from in vitro and in vivo applications, considering not only the already established PET ligands but also the recently published preclinical work. Copyright © 2013 John Wiley & Sons, Ltd.